Penggabungan Model Servqual dan Kano untuk Mengukur Kepuasan Pelanggan terhadap Layanan Swab dan PCR - Irawati, Desrina Yusi; Junita, Elisabet (Universitas Katolik Parahyangan, 2024)
Swabs and PCR are ways to track patients infected with COVID-19. One private swab and PCR service provider in Surabaya offers swab and PCR tests with fast results and is open 24 hours a day. This research aims to determine service quality performance, identify the causes of consumer dissatisfaction, and identify service attributes that must be maintained and improved for Swab and PCR services in Surabaya. This research uses an integration of the Servqual and Kano methods. The integration of Servqual and Kano determines the service attributes to be improved. Data was obtained from a questionnaire using the five-dimensional Servqual approach, then calculated to get a gap value and categorized using the Blauth formula. The Servqual gap and the Blauth formula's category values are combined to make action decisions. The results state that swab and PCR service providers still need to improve all factors used in this research. Three attributes fall into the weak and indifferent category, so the decision that needs to be made is to ignore them because they do not affect consumer satisfaction and are not a priority for improvement. The other twenty-one attributes fall into the weak and one-dimensional category, meaning companies must improve these attributes to satisfy consumers. Companies need to make improvements to ensure better service, including increasing the number of medical officers to reduce fatigue and queues and providing training on medical procedures and communication skills for medical officers.